1982
DOI: 10.1016/s0022-5347(17)53293-0
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Carcinoma of the Prostate at the Time of Transurethral Resection: Importance of Evaluating Every Chip

Abstract: Incidental adenocarcinoma of the prostate has been divided into stage A1--less than 3 foci of well differentiated adenocarcinoma present and stage A2--3 or more foci of poorly differentiated tumor present. The clinical significance of these 2 stages has been well documented, with stage A1 lesions causing no increased mortality, while up to 30 per cent of patients with clinical stage A2 disease will have positive pelvic lymph nodes at exploration and, thus, will have surgical stage D1 tumor. Most pathology labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 15 publications
0
22
0
1
Order By: Relevance
“…The presence of carcinoma in a TUR specimen may signify extensive spread from the periphery of the gland. The probability of detecting carcinoma in TUR specimens is directly related to the amount of sampling (Newman et al, 1982). If five to eight blocks are submitted, all clinical stage T1b carcinomas are detected, and if eight to ten blocks are submitted, more than 90% stage T1a carcinomas are detected (Murphy et al, 1986;Vollmer 1986;Eble and Epstein, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of carcinoma in a TUR specimen may signify extensive spread from the periphery of the gland. The probability of detecting carcinoma in TUR specimens is directly related to the amount of sampling (Newman et al, 1982). If five to eight blocks are submitted, all clinical stage T1b carcinomas are detected, and if eight to ten blocks are submitted, more than 90% stage T1a carcinomas are detected (Murphy et al, 1986;Vollmer 1986;Eble and Epstein, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…This confirms that se lective sampling of yellow chips is worthwhile [20][21][22]. The sensitivity of naked-eye examination for malignancy was probably overestimated, as some small-volume tu mours may have been missed due to partial sampling [4][5][6][7], However, this would not change specificity and posi tive predictive value.…”
Section: Discussionmentioning
confidence: 55%
“…This usually finds all large-volume prostatic adenocarcinomas, but will miss some small-volume tumours [4][5][6][7], The yield of small-volume tumours can be increased by complete sampling [4][5][6][7] and also by step-sectioning techniques [8. 9], However, these increase laboratory work load, and the clinical significance of low-grade small-volume prostatic adenocarcinoma is disputed.…”
Section: Introductionmentioning
confidence: 99%
“…This is in accor dance with the incidence in other series. [4,8,14,18,19], Newman et al [ 18] found that when all material was processed, the detection of incidental prostatic cancer increased from 8 to 14%. Others [8,20,21] have found that partial sampling is adequate to detect most inciden tal cancers.…”
Section: (9) 11 (4) 4(0) 7(1)mentioning
confidence: 99%